Disturbances in the gut microbiota potentially associated with metabolic syndrome among patients living with HIV-1 and on antiretroviral therapy at Bafoussam Regional Hospital, Cameroon - Joël Martial Diesse; Sushama Jadhav; Stephen Lacmata Tamekou; Gustave Simo; Jean Paul Dzoyem; Jacob Souopgui; Jules-Roger Kuiate; Vijay Nema (Diabetology & Metabolic Syndrome)
Abstract Background This study investigates the gut microbiota components associated with metabolic syndrome in patients living with HIV-1 at Bafoussam Regional Hospital, West Cameroon, it focuses on gastrointestinal mucosal barrier disruption and dysbiosis, and their effects on persistent inflammation and metabolic disorders. Methods A pilot study was conducted involving fourteen patients living with HIV-1. The patients were divided into two groups of seven in each group. One group consisted of patients with metabolic syndrome, and the other group included patients without metabolic syndrome. Gut microbiota was characterized using 16 S rRNA gene-targeted sequencing to analyze microbial diversity and composition. Beta diversity and the relative abundance of bacterial taxa were compared between patients with and without metabolic syndrome. Results Patients living with HIV-1 and metabolic syndrome showed significantly altered beta diversity compared to those without metabolic syndrome. A higher relative abundance of Firmicutes and increased proliferation of Proteobacteria were observed in patients with metabolic syndrome. Additionally, a decrease in metabolically beneficial bacteria, such as Bifidobacterium sp., Lactobacillus sp., Akkermansia sp., and Faecalibacterium sp., was noted. Several beneficial bacterial species were associated with participants' metadata, suggesting potential links between gut microbiota and metabolic syndrome. Conclusion This preliminary study highlights that gut microbial balance, rather than the presence of specific bacteria, plays a crucial role in managing metabolic health in patients living with HIV-1. The altered gut microbiota in participants with metabolic syndrome emphasizes the need for further research into the optimal gut microbial structure. Understanding the interaction between gut microbiota changes and the chemical environment in these patients could guide targeted interventions to improve metabolic outcomes.